Effect of heat treatment on the structural modification of neodymium doped tellurite glass - Mat Jan, Nur Amanina Mat (National Institute R and D of Materials Physics, 2016)
Neodymium doped tellurite nanostructured glass having a composition of (75-x)TeO2-15MgO-10Na2O-(x)Nd2O3, where 0 ≤ x ≤ 2.5 mol% has successfully been prepared by melt-quenching technique. The structure of crystallisation is determined using XRD technique and the existence of nanocrystalline nature of this glass is confirmed by TEM analyser. The physical properties of glass has been determined while their structural modification has been investigated using the IR and Raman spectroscopy analysis. The IR studies has shown that the structure of glass network consists of bending vibrations of Te-O-Te while, some structural units are TeO4, TeO3+1, and TeO3 units.